Hedging with forwards and puts in complete and incomplete markets - Benninga, Simon Z.; Oosterhof, Casper M. (Journal of Banking & Finance, 2004)
We derive general conditions for forward and/or put unbiasedness and show that restrictions on the probability distribution suffice for simultaneous unbiasedness of forwards and puts, even if consumers are assumed to be risk averse. We examine the optimal production and hedging decisions by a risk-averse producer. If the producer’s state prices are derived from his marginal rates of substitution, an unbiased market forward price is perceived as overpriced and an unbiased market put price as underpriced. Even in this case the full hedging and separation theorems still hold and, contrary to previous literature, there is a hedging role for puts.